2017
DOI: 10.1111/cpr.12411
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulates cisplatin‐induced stemness and chemoresistance via the upregulation of CD44, ABCB1 and ADAM17 in oral squamous cell carcinoma

Abstract: Objective: We inspected the relevance of CD44, ABCB1 and ADAM17 in OSCC stemness and deciphered the role of autophagy/mitophagy in regulating stemness and chemoresistance. Material and methods:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 41 publications
5
49
0
Order By: Relevance
“…Emerging evidences have illustrated the important roles of cancer stem‐like cells (CSC) in human tumours, including OSCC . In present study, our team aims to investigate the biological role of SNHG20 on the stemness and tumorigenesis of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences have illustrated the important roles of cancer stem‐like cells (CSC) in human tumours, including OSCC . In present study, our team aims to investigate the biological role of SNHG20 on the stemness and tumorigenesis of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported that oxaliplatin-induced autophagy enriches the population of colorectal CD44 + CSCs and maintain the stemness of colorectal CSCs, this protection eventually causes chemoresistance in colorectal CSCs , and so did Nail's group. They found that autophagy regulates the expression of stemness surface marker CD44, drug resistance marker ABCB1 and invasion mediator ADAM17 to help maintain stemness and chemoresistance, but the mechanism remains unclear (Naik et al, 2018). Targeting autophagy to diminish the CSCs subpopulation might be a new direction to overcome platinum resistance.…”
Section: Autophagymentioning
confidence: 99%
“…As described above, autophagy during treatment may reduce sensitivity to cytotoxic therapy. Correspondingly, resistance to various types of therapy is characterized by enhanced basal levels of autophagy, as defined by increased conversion of LC3‐I to LC3‐II, increased numbers of LC3B puncta per cell, upregulated numbers of autophagolysosomes, and degradation of p62 . For example, cisplatin‐resistant clones of ovarian cancer cell lines as well as an oral squamous cell carcinoma cell line were characterized by enhanced levels of autophagic flux .…”
Section: Part I: the Role Of Autophagy In Cancer Cellsmentioning
confidence: 99%